STRUCTURAL PECULIARITIES OF THE ARTERIES IN CONDITIONS OF COLD FACTOR - Фарадж Мусбах Ельмезугі,; Popadynets, O.H.; Sobol, L.V.; Dubyna, N.M. (World of Medicine and Biology, 2016)
This work is devoted to the study of peculiarities of morphofunctional changes in the structural elements of the arterial walls of muscular type under the influence of the general deep hypothermia. There were used 20 white outbred mature rats weighing 160-180 g. Cooling was performed in accordance with the patented method. Euthanasia of rats – was carried out by overdose of ether anesthesia. Sampling of the material was performed immediately after the exposure to the general deep hypothermia and during the 1st, 3rd, 7th day of posthypothermic period. At the height of the impact of cold factor and during the 1st, 3rd day swelling and partial damage of certain cellular and extracellular components of the arterial wall are observed. During the 7th day degenerative changes of the structural components of the vascular wall prevail.
Keywords: arteries of muscular type; general hypothermia